Examining Small Intestinal Transit Time as a Function of Age: Is There Evidence to Support Age-Dependent Differences among Children? - Maharaj, Anil R; Edginton, Andrea N (Drug metabolism and disposition, 2016)
The small intestine represents the region where the majority of drug and nutrient absorption transpires. Among adults, small intestinal transit kinetics is well delineated; however, the applicability of these values toward children remains unclear. This article serves to examine the relationship between age and mean small intestinal transit time (SITT) based on the available literature. In addition, the influence of alterations in intestinal transit time was explored among children using a model-based approach. Primary literature sources depicting SITT from children to adults were ascertained via the PubMed database. Data were limited to subjects without pathologies that could influence intestinal motility. Random-effect meta-regression models with between-study variability were employed to assess the influence of age on SITT. Three separate models with age as a linear or higher-order (i.e., second- and third-order polynomial) regressor were implemented to assess for the potential of both linear and curvilinear relationships. Examination of the influence of altered intestinal transit kinetics on the absorption of a sustained release theophylline preparation was explored among children between 8 and 14 years using physiologically based pharmacokinetic (PBPK) modeling. Age was not found to be a significant modulator of small intestinal transit within either the linear or higher-order polynomial meta-regression models. PBPK simulations indicated a lack of influence of variations in SITT on the absorption of theophylline from the examined sustained release formulation in older children. Based on the current literature, there is no evidence to suggest that mean SITT differs between children and adults.